Multilocus Sequence Typing and Population Genetic Analysis of Enterocytozoon bieneusi: Host Specificity and Its Impacts on Public Health - Li, Wei; Xiao, Lihua (Frontiers in Genetics, 2019)
Microsporidia comprise a large class of unicellular eukaryotic pathogens that are medically and agriculturally important, but poorly understood. There have been nearly 1,500 microsporidian species described thus far, which are variable in biology, genetics, genomics, and host specificity. Among those, Enterocytozoon bieneusi is the well-known species responsible for the most recorded cases of human microsporidian affections. The pathogen can colonize a broad range of mammals and birds and most of the animals surveyed share some genotypes with humans, posing a threat to public health. Based on DNA sequence analysis of the ribosomal internal transcribed spacer (ITS) and phylogenetic analysis, several hundreds of E. bieneusi genotypes have been defined and clustered into different genetic groups with varied levels of host specificity. However, single locus-based typing using ITS might have insufficient resolution to discriminate among E. bieneusi isolates with complex genetic or hereditary characteristics and to assess the elusive reproduction or transmission modes of the organism, highlighting the need for exploration and application of multilocus sequence typing (MLST) and population genetic tools. The present review begins with a primer on microsporidia and major microsporidian species, briefly introduces the recent advances on E. bieneusi ITS genotyping and phylogeny, summarizes recent MLST and population genetic data, analyzes the inter- and intragroup host specificity at the MLST level, and interprets the public health implications of host specificity in zoonotic or cross-species transmission of this ubiquitous fungus.